2019
DOI: 10.1186/s12891-019-2630-0
|View full text |Cite
|
Sign up to set email alerts
|

Cage positioning as a risk factor for posterior cage migration following transforaminal lumbar interbody fusion – an analysis of 953 cases

Abstract: Background The risk of posterior cage migration (PCM) exists when a fusion cage is used for transforaminal lumbar interbody fusion (TLIF). This complication is influenced by contact pressure between the endplate and the cage. Previous reports demonstrated that anteriorly located cages bore more load and had greater strain than posteriorly located cages. However, there have been no detailed reports on the correlation between cage positioning and PCM. Methods From March 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
46
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(54 citation statements)
references
References 22 publications
2
46
0
Order By: Relevance
“…Park et al [ 3 ] also reported that posterior cage positioning was a significant factor for CR. Here, we used quantitative measurements introduced by Hu et al [ 8 ] to evaluate cage positioning. In accordance with their results, [ 8 ] we found that sagittal, but not coronal cage positioning was correlated with CR.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Park et al [ 3 ] also reported that posterior cage positioning was a significant factor for CR. Here, we used quantitative measurements introduced by Hu et al [ 8 ] to evaluate cage positioning. In accordance with their results, [ 8 ] we found that sagittal, but not coronal cage positioning was correlated with CR.…”
Section: Discussionmentioning
confidence: 99%
“…Here, we used quantitative measurements introduced by Hu et al [ 8 ] to evaluate cage positioning. In accordance with their results, [ 8 ] we found that sagittal, but not coronal cage positioning was correlated with CR. Biomechanical studies demonstrated that constructs with anterior cage placement were significantly stiffer than those with posterior cage placement, and that the cage shared more load under axial compression with anterior cage placement than with posterior cage placement.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The fusion stability is critically affected by suitable positioning of the pedicle screw [ 12 ], and therefore, continuous effort is being made to improve screw design. The selection and placement of the interbody cage material also impacts the stability and efficacy of TLIF [ 13 , 14 , 15 ]. Progresses have been made to improve the surgical procedure, materials, and instrument to reduce the length of stay and radiation exposure during MIS-TLIF, as prolonged exposure may adversely affect patient’s health and recovery time [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the decompression of dura and the nerve root was performed under endoscope and INM, avoiding nerve injury and improving the safety of operation.Literature reports suggest that smaller fusion cages must be used when endoscope-guided intrabody cages are placed, because traditional fusion cages are too large to pass through working channels[5,16]. However, the undersized cage may directly cause cage migration into the intervertebral foramen or spinal canal, thus leading to neurological compromise, failure of fixation, or even revision operation[17,18]. The ZELIF technology uses a specially designed C-shaped open channel, which can realize the installation of conventional cages under fluoroscopy without size reduction.…”
mentioning
confidence: 99%